2023
DOI: 10.3390/pathogens12020163
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination and Alcohol Consumption: Justification of Risks

Abstract: Since the beginning of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, pharmaceutical companies and research institutions have been actively working to develop vaccines, and the mass roll-out of vaccinations against COVID-19 began in January 2021. At the same time, during lockdowns, the consumption of alcoholic beverages increased. During the peak of vaccination, consumption remained at high levels around the world, despite the gradual relaxation of quarantine restrictions. Two of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…This shift may help to explain the decrease in reports of higher alcohol consumption in the second and third waves. Alcohol is known to exacerbate illness; hence vaccination may have decreased the risks of drinking for vaccinated individuals [ 34 ]. Although vaccine hesitancy may have increased anxiety when COVID-19 vaccines first became available [ 35 ], Chen and the co-authors similarly found that vaccination for COVID-19 was associated with a decrease in anxiety and depression symptoms [ 36 ], which may help to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…This shift may help to explain the decrease in reports of higher alcohol consumption in the second and third waves. Alcohol is known to exacerbate illness; hence vaccination may have decreased the risks of drinking for vaccinated individuals [ 34 ]. Although vaccine hesitancy may have increased anxiety when COVID-19 vaccines first became available [ 35 ], Chen and the co-authors similarly found that vaccination for COVID-19 was associated with a decrease in anxiety and depression symptoms [ 36 ], which may help to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of alcoholic beverages increased during lockdowns and remained at high levels during the peak of vaccination, especially among young people. It has been postulated that alcohol consumption, known to affect expression of ACE2, may have contributed to increasing the “Spike effect” risk of COVID-19 vaccines [ 104 ]. Finally, if ACE2 and Ang II clearly play a role in the thrombosis and cardiovascular complications following the COVID-19 mRNA vaccine, it has also been suggested that another physiopathological mechanism can sometimes trigger the cerebral venous sinus thrombosis (CVST) and cerebral venous thrombosis observed after vaccination with an adenoviral-vector-based vaccine [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two potential explanations are as follows: first, excessive alcohol intake may modulate immunity, potentially reducing COVID-19 vaccine effectiveness. 48 Second, it could be a defense mechanism against increasing anxiety and stress from COVID-19 pandemic-related social circumstances, possibly decreasing it. Following the global lockdown, alcohol consumption significantly increased, 48 49 particularly in South Korea, where drinking is a popular leisure activity linked to peer pressure.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Second, it could be a defense mechanism against increasing anxiety and stress from COVID-19 pandemic-related social circumstances, possibly decreasing it. Following the global lockdown, alcohol consumption significantly increased, 48 49 particularly in South Korea, where drinking is a popular leisure activity linked to peer pressure. 32 49 In a study of middle-aged Korean adults during the COVID-19 pandemic, higher friend support led to excessive alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%